A revision of Episothalma Swinhoe, 1893, with descriptions of two new species and one new genus (Lepidoptera, Geometridae, Geometrinae) - Xue, Dayong; Wang, Xuejian; Han, Hongxiang (Zootaxa, 2009)
The genus Episothalma Swinhoe is reviewed, and two new species are described: E. irrobustaria, sp. nov. from Thailand, and E. cuspidata sp. nov. from Hainan Province, China. E. ocellata Swinhoe is excluded from Episothalma and Pseudepisothalma gen. nov. is erected based on this species. A lectotype is designated for P. ocellata. Descriptions and diagnoses for both genera are given. All the known species are redescribed, and variations in the male genitalia of E. robustaria (Guenée) are described and figured. Illustrations of adults and genitalia are presented.